MODEL PEMBELAJARAN GEOGRAFI DENGAN PENDEKATAN SCIENTIFIC PADA SMA NEGERI 1 DAN SMA NEGERI 2 BANJARMASIN - Ferryska Widiaswara (Universitas Lambung Mangkurat, 2013)
The learning process is a combination of scientific learning process which originally focused on the exploration, elaboration, and confirmation comes by observing, ask, try, reasoning, and this mengomunikasikan.Penelitian discuss geography learning model with a scientific approach to the two high schools in the city of Banjarmasin designated as a pilot project to implement the curriculum in 2013 the SMA SMA N 1 and N 2 Banjarmasin start of the school year 2013/2014. This study uses qualitative descriptive method and implemented at SMAN 1 and SMAN 2 Banjarmasin. The results showed that teachers' understanding of the scientific approach is not maximized so the impact on the application. However, teachers also know the purpose of scientific approaches used in the curriculum of 2013, which is to form the character of the students and make students more active. Besides scientific approach is also beneficial to stimulate students to use all the senses are owned in learning. Key words: Models of teaching. Geography, Scientific approach